(untitled) (Editora Impacto Científico, 2025)
The increase in oil spills due to human activities represents a serious threat to aquatic ecosystems. Chitosan, a biopolymer obtained from the deacetylation of chitin from crustacean waste, has stood out as a sustainable material for hydrocarbon removal. Its biodegradability, chemical functionality, and structural modification possibilities allow for the development of selective, oleophilic sorbents with high adsorption capacity. In Brazil, the high volume of waste from shrimp farming, especially in the North and Northeast regions, offers significant potential for chitosan production, strengthening the bioeconomy and reducing environmental impacts. Studies indicate that, although native chitosan shows moderate performance, derived composites and aerogels exhibit greater efficiency, rapid adsorption kinetics, and reuse potential. Furthermore, the use of crustacean waste strengthens its economic and environmental viability. Therefore, chitosan represents a promising alternative for sustainable oil spill mitigation strategies. DOI: https://doi.org/10.56238/edimpacto2025.090-049